Efektivitas Malacca Strait Patrol dalam Mengatasi Pembajakan dan Perampokan Bersenjata di Perairan Selat Malaka (2009-2014) - Adiputro, Try Istiawan; Windiani, Reni; Pattipeilohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The Malacca Strait is a strategic lane under the sovereignty of four countries in Southeast Asia: Indonesia, Malaysia, Singapore and Thailand, which are highly vulnerable to maritime crimes, such as piracy and armed robbery against ships. Indonesia Malaysia, Singapore, and Thailand are litoral states, which are fully responsible for everything that happens in the region. Piracy and armed robbery in the Malacca Strait are detrimental to litoral states and user states on the economic, economic, security and sovereignty aspects. The purpose of this research is to determine the effectiveness of Malacca Strait Patrol in combating piracy and robbery in Malacca Strait 2009-2014. In this research, the researcher used institutional neo-liberal theory to analyze the effectiveness of Malacca Strait Patrol on each indicator of source or input approach, process approach, and target or output approach. The method of research is descriptive qualitative method, and doing technique of data collection of literature study and interview. The result of this research is that Malacca Strait Patrol has been successful and effective in combating piracy and armed robbery in the Malacca Strait based on the indicator of effectiveness on source or input approaches, process approaches, and target or output approaches. Litoral states have implemented all of the terms of reference (TOR) and standard operating procedures (SOP) of Malacca Strait Patrol (MSP) properly and correctly, so that the incidents of piracy and armed robbery in the Strait of Malacca can be minimalized.